2016
DOI: 10.1016/j.aspen.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic ash decreases dehydration tolerance in the field cricket Gryllus bimaculatus (Orthoptera: Gryllidae)

Abstract: Made available through Montana State University's ScholarWorks scholarworks.montana.edu Volcanic ash decreases dehydration tolerance in the field cricket Gryllus bimaculatus (Orthoptera: Gryllidae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Previous studies on insecticidal activity of volcanic ash in laboratory exposure bioassays on Oryzaephilus surinamensis (L.) (Coleoptera: Silvanidae), Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), Sitophilus oryzae (L.) (Coleoptera: Curculionidae), and Dichroplus vittigerum (Blanchard) (Orthoptera: Acrididae) have shown the acute insecticidal effect of volcanic ash from Puyehue Cordon Caulle through contact toxicity (Buteler et al 2011;Buteler et al 2014;Fernández-Arhex et al 2016). Kuriwada & Reddy (2016) found that the fallen ash adheres to the surface of plants and insects. The fallen ash has been reported to have reduced dehydration tolerance (Kuriwada & Reddy 2016) and mating behavior in the field cricket Gryllus bimaculatus (De Geer) (Orthoptera: Gryllidae).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on insecticidal activity of volcanic ash in laboratory exposure bioassays on Oryzaephilus surinamensis (L.) (Coleoptera: Silvanidae), Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), Sitophilus oryzae (L.) (Coleoptera: Curculionidae), and Dichroplus vittigerum (Blanchard) (Orthoptera: Acrididae) have shown the acute insecticidal effect of volcanic ash from Puyehue Cordon Caulle through contact toxicity (Buteler et al 2011;Buteler et al 2014;Fernández-Arhex et al 2016). Kuriwada & Reddy (2016) found that the fallen ash adheres to the surface of plants and insects. The fallen ash has been reported to have reduced dehydration tolerance (Kuriwada & Reddy 2016) and mating behavior in the field cricket Gryllus bimaculatus (De Geer) (Orthoptera: Gryllidae).…”
Section: Introductionmentioning
confidence: 99%
“…Kuriwada & Reddy (2016) found that the fallen ash adheres to the surface of plants and insects. The fallen ash has been reported to have reduced dehydration tolerance (Kuriwada & Reddy 2016) and mating behavior in the field cricket Gryllus bimaculatus (De Geer) (Orthoptera: Gryllidae). The present study investigated the potential for chronic dietary intake and sub-lethal effects of volcanic ash given that most studies have assessed contact toxicity.…”
Section: Introductionmentioning
confidence: 99%